The Influence of Gender Bias: Is Pain Management in the Field Affected by Health Care Provider's Gender?. Issue 5 (4th October 2022) - Karas, Adi; Fridrich, Lidar; Radomislensky, Irina; Avital, Guy; Gendler, Sami; Chen, Jacob; Gelikas, Shaul; Benov, Avi
Abstract: Introduction: Appropriate pain management indicates the quality of casualty care in trauma. Gender bias in pain management focused so far on the patient. Studies regarding provider gender are scarce and have conflicting results, especially in the military and prehospital settings. Study Objective: The purpose of this study is to investigate the effect of health care providers' gender on pain management approaches among prehospital trauma casualties treated by the Israel Defense Forces (IDF) medical teams. Methods: This retrospective cohort study included all trauma casualties treated by IDF senior providers from 2015-2020. Casualties with a pain score of zero, age under 18 years, or treated with endotracheal intubation were excluded. Groups were divided according to the senior provider's gender: only females, males, or both female and male. A multivariate analysis was performed to assess the odds ratio of receiving an analgesic, depending on the presence of a female senior provider, adjusting for potential confounders. A subgroup analysis was performed for "delta-pain, " defined as the difference in pain score during treatment. Results: A total of 976 casualties were included, of whom 835 (85.6%) were male. Mean pain scores (SD) for the female only, male only, and both genders providers were 6.4 (SD = 2.9), 6.4 (SD = 3.0), and 6.9 (SD = 2.8), respectively (P = .257). There was no significant difference between females, males, or both female and male groups in analgesic treatment, overall and per specific agent. This remained true also in the multivariate model. Delta-pain difference between groups was also not significant. Less than two-thirds of casualties in this study were treated for pain among all study groups. Conclusion: This study found no association between IDF Medical Corps providers' gender and pain management in prehospital trauma patients. Further studies regarding disparities in acute pain treatment are advised.